Sickness Status and Neural Tube Defects: A Case–Control Study in a North Indian Population. Issue 17 (9th October 2017) - Deb, Roumi; Arora Gupta, Jyoti; Saraswathy, Kallur N.; Kalla, Aloke K.
Abstract : Background: The prevalence of neural tube defects (NTDs) in India is high in comparison to other regions in the world, with the Northern part reporting the highest prevalence. Methods: To explore the risk factors for NTDs, a case–control study was carried out in Delhi from January 2008 to June 2011. Using multivariate logistic regression model analysis, 308 cases were compared with 580 controls and adjusted odds ratio (AOR) was calculated using SPSS version 17. Results: Maternal factors that were significantly associated with increased risk of NTDs were inter‐pregnancy interval (AOR = 3.175; 95% confidence interval [CI], 2.007–5.024), hyperthermia during the first trimester (AOR = 2.07; 95% CI, 1.131–3.788), maturation ill pregnancy (AOR = 1.956; 95% CI, 1.385–2.763), chronic illness (AOR = 1.648; 95% CI, 1.103–2.462), and use of antibiotics (AOR = 5.589; 95% CI, 1.789–17.455). Differences in the risk were also found between upper and lower NTD. It was observed that all of the former five variables, except for chronic illness, were associated with risk for upper NTDs (AOR = 1.532; 95% CI, 0.916–2.563). In contrast, hyperthermia before conception (and not during the first trimester) was found to be additionally associated with risk for lower NTDs (AOR = 2.782; 95% CI, 1.302–5.944). Conclusion: These findings highlight heterogeneity in the etiology of upper and lower NTDs. The study also highlights the risk factors that should be considered in combating the risk of NTDs. Birth Defects Research 109:1393–1399, 2017.© 2017 Wiley Periodicals, Inc.